1995
DOI: 10.3181/00379727-210-43937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Ultrasound Exposure on Adult Offspring Behavior in the Wistar Rat

Abstract: An ultrasound exposure tank was specifically designed for experimental bioeffects studies. Thirty-six pregnant rats were anesthetized, immersed to the axilla in a water tank, and exposed on Day 15, 17, and 19 of gestation. Twelve rats were exposed to 5.0 MHz pulsed ultrasound of effective pulse duration equal to approximately 0.170 microseconds, pulse repetition rate (PRF) 1 kHz, and a spatial peak, temporal peak intensity (lsptp) of 500 W/cm2, representing a clinically appropriate exposure level. The spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…It is important to mention that there exist studies showing negative results after prenatal ultrasound exposure. As an example, Jensh et al [] found that rats exposed to 35 minutes of ultrasound in utero did not exhibit any changes in memory and anxiety tests.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that there exist studies showing negative results after prenatal ultrasound exposure. As an example, Jensh et al [] found that rats exposed to 35 minutes of ultrasound in utero did not exhibit any changes in memory and anxiety tests.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the aforementioned publications, the results of a study by Jensh et al [33] did not indicate changed behavior after prenatal exposure to ultrasound.…”
Section: Animal Experimentsmentioning
confidence: 60%
“…Anders als in den vorgenannten Publikationen ließ das Ergebnis einer Studie von Jensh et al[33] nicht auf ein verändertes Verhalten nach pränataler Ultraschallexposition schließen. Die Gruppe hatte trächtige Ratten an den Gestationstagen 15, 17 und 19 für jeweils 35 Minuten mit einer für den B-Mode üblichen SPTA-Leistung von 24 mW/cm² exponiert und in einem zweiten Schritt die Leistungsabgabe auf etwa den doppelten Wert erhöht.…”
unclassified
“…Finally, Ang, Gluncic, Duque, Schafer, and Rakic [] observed that mice exposed to 30 min or more of ultrasound on day E14.5 experienced significantly disrupted cortical neuronal migration relative to sham controls. [It is worth noting that there exist negative results, for example, Jensh et al., found no alterations of the memory and anxiety level of rats after 35 min of in utero ultrasound exposure.] To our knowledge, there do not exist any studies that assess possible changes in social behavior induced by ultrasound delivered in utero.…”
Section: Introductionmentioning
confidence: 99%